Women's gambling behaviour, product preferences, and perceptions of product harm: Differences by age and gambling risk status - McCarthy, S.; Thomas, S.; Randle, M.; Bestman, A.; Pitt, H.; Cowlishaw, S.; Daube, Mike (BioMed Central, 2018)
Background: Women's participation in, and harm from gambling, is steadily increasing. There has been very limited research to investigate how gambling behaviour, product preferences, and perceptions of gambling harm may vary across subgroups of women. Methods: This study surveyed a convenience sample of 509 women from Victoria and New South Wales, Australia. Women were asked a range of questions about their socio-demographic characteristics and gambling behaviour. Focusing on four gambling products in Australia-casino gambling, electronic gambling machines (EGMs), horse betting, and sports betting-women were asked about their frequency of participation, their product preferences, and perceptions of product harms. The sample was segmented a priori according to age and gambling risk status, and differences between groups were identified using Chi-square tests and ANOVAs. Thematic analysis was used to interpret qualitative data. Results: Almost two thirds (n=324, 63.7%) of women had engaged with one of the four products in the previous 12 months. Compared to other age groups, younger women aged 16-34 years exhibited a higher proportion of problem gambling, gambled more frequently, and across more products. While EGMs were the product gambled on most frequently by women overall, younger women were significantly more likely to bet on sports and gamble at casinos relative to older women. Qualitative data indicated that younger women engaged with gambling products as part of a 'night out', 'with friends', due to their 'ease of access' and perceived 'chance of winning big'. There were significant differences in the perceptions of the harms associated with horse and sports betting according to age and gambling risk status, with younger women and gamblers perceiving these products as less harmful. Conclusions: This study highlights that there are clear differences in the gambling behaviour, product preferences, and perceptions of product harms between subgroups of women. A gendered approach will enable public health researchers and policymakers to ensure that the unique factors associated with women's gambling are taken into consideration in a comprehensive public health approach to reducing and preventing gambling harm.